2013
DOI: 10.1016/j.ajo.2012.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Amblyopia in Childhood Eyelid Ptosis

Abstract: Purpose To report the prevalence and causes of amblyopia among children with ptosis diagnosed in a well-defined population over a 40-year period. Design Retrospective, population-based cohort study. Methods We retrospectively reviewed the charts of one hundred and seven patients (< 19 years) for the prevalence and causes of amblyopia who were diagnosed with childhood ptosis as residents of Olmsted County, Minnesota, from January 1, 1965, through December 31, 2004. Results Amblyopia was diagnosed in 16 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 19 publications
2
37
2
2
Order By: Relevance
“…Our study revealed that the upper palpebral fold was absent in 38.4% of cases, which was contrary to the observations with some authors [4,6] who found the palpebral bulge generally in good position. It should be noticed, however, that this information lacks in many of the patients in our series (30.1%).…”
Section: Clinical Presentationcontrasting
confidence: 57%
See 2 more Smart Citations
“…Our study revealed that the upper palpebral fold was absent in 38.4% of cases, which was contrary to the observations with some authors [4,6] who found the palpebral bulge generally in good position. It should be noticed, however, that this information lacks in many of the patients in our series (30.1%).…”
Section: Clinical Presentationcontrasting
confidence: 57%
“…This proportion is much lower than that observed in the literature [4,6], which notes the predominance of congenital ptosis in 75% of cases, probably due to parents' ignorance.…”
Section: Etiological Presentationcontrasting
confidence: 52%
See 1 more Smart Citation
“…Both cases were in children with exotropia and in each case the amblyopia was secondary to strabismus. 5 …”
Section: Resultsmentioning
confidence: 99%
“…The incidence and demographics of this population of children with eyelid ptosis and the prevalence of amblyopia have been previously reported. 4,5 …”
Section: Methodsmentioning
confidence: 99%